Immunological monitoring of brain tumour patients - Nayak, Ashok; S. M., Sajith Babu; Singh, Lal Mani (International Surgery Journal, 2018)
Background: Patient suffering from CNS tumours are among the best suited as regards the study of their immunologic status is concerned because these tumours rarely metastasize and general condition of patient is not much affected. Extensive research has been done on immunological response in neoplasms of other organs, but immunology of CNS tumours studied mainly during last five decades. It is now realized that immunologic reactions may be important in the development and growth of the CNS tumours. Although there is evidence that immunotherapy is helpful in control of some solid tumours but adequate knowledge of the immunology of glial tumours to guide the rational treatment is not yet available. Methods: This study was conducted on 60 cases that included 20 controls and 40 patients of primary intracranial brain tumors admitted to neurosurgical services of University Hospital, Banaras Hindu University, Varanasi during the period of January 1987 to January 1988. Results: The study revealed, medulloblastoma and glioblastoma or anaplastic astrocytoma show more marked suppression of cell mediated immunity than astrocytoma grade +II and other malignant tumour subgroups. In case of humoral immune response, antigen of brain tumours elicit an Ig M response rather IgG response which is commonly elicited in other neoplasia. Conclusions: The results regarding Ig M, and Ig G levels are in agreement with most of the other studies. It appears that antigen of brain tumours elicits an Ig M response rather IgG response which is commonly elicited in other neoplasia.